2019
DOI: 10.1007/s00204-019-02599-z
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated aluminium exposure: risk assessment for the general population

Abstract: Aluminium is one of the most abundant elements in earth's crust and its manifold uses result in an exposure of the population from many sources. Developmental toxicity, effects on the urinary tract and neurotoxicity are known effects of aluminium and its compounds. Here, we assessed the health risks resulting from total consumer exposure towards aluminium and various aluminium compounds, including contributions from foodstuffs, food additives, food contact materials (FCM), and cosmetic products. For the estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 52 publications
(56 reference statements)
1
56
0
1
Order By: Relevance
“…Tietz et al assessed the health risks resulting from total consumer exposure to Al. The mean dietary intake for the German adult aged 14-80 years of age range between 0.18 and 0.21 mg/kg-bw/wk [32]. On the other hand, available studies indicate that low dose of chronic exposure to Al compounds may have the potential to induce some behavioral changes, brain aging and neurodegeneration in experimental mice or rats [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tietz et al assessed the health risks resulting from total consumer exposure to Al. The mean dietary intake for the German adult aged 14-80 years of age range between 0.18 and 0.21 mg/kg-bw/wk [32]. On the other hand, available studies indicate that low dose of chronic exposure to Al compounds may have the potential to induce some behavioral changes, brain aging and neurodegeneration in experimental mice or rats [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…10) and whole milk (25.89), respectively. Although studies have documented Al content in infant formula could be an important source of exposure for the 0-3 years [32,33], in Taiwan, infant formula diet has not been recorded to cause any effects on health. On the other hand, Al-containing adjuvants for children in vaccines have been suspected of causing effects, which include neurotoxicity and the autism spectrum, however, findings of an evidence-based meta-analysis of case-controlled studies suggest that vaccinations are not associated with the development of autism [34].…”
Section: Discussionmentioning
confidence: 99%
“…The use of sodium aluminium silicate (E 554) as a food additive is expected to contribute to the dietary exposure to aluminium for which a TWI of 1 mg/kg bw per week has been established (EFSA, 2008). As aluminium intakes from the diet may exceed the TWI (EFSA, 2008;Tietz et al, 2019), exposure to aluminium from the use of sodium aluminium silicate (E 554) at the reported use levels was calculated considering that the food additive could contain up to 7.8% of aluminium (from the maximum amount of 15% of Al 2 O 3 according to EU specifications (Table 1)).…”
Section: Exposure To Sodium Aluminium Silicate (E 554)mentioning
confidence: 99%
“…Further to this, the use of Al-containing food additives is restricted by the recommendation of the European Food Safety Authority (EFSA) to lower the tolerable weekly intake (TWI) of Al to ≤1 mg/kg body weight. However, it was suggested that this TWI might be significantly exceeded, especially in children [6].…”
Section: Introductionmentioning
confidence: 99%